POTENTIAL VULNERABILITY OF BULL MOOSE IN CENTRAL BRITISH COLUMBIA TO THREE ANTLER-BASED HUNTING REGULATIONS - Child, Kenneth; Aitken, Daniel A; Rea, Roy V; Demarchi, R A (Lakehead University, 2010)
Antlers from bull moose (Alces alces andersoni) harvested in the Omineca sub-region of central British Columbia were submitted by hunters for inspection, measurement, and comparison by age in 1982-1989. After correcting for non-reporting bias, we examined the potential vulnerability of these moose (n = 1,886) to 3 antler-based hunting regulations currently advertised in British Columbia: spike/fork (S/F), tripalm (TP), and 10 point (10PT). The S/F regulation put 15.9% of bulls at risk, and the TP and 10PT regulations put 11.1% and 12.0% at risk, respectively. Bulls with cervicorn antlers were at higher risk (41.3%) to the S/F regulation than the TP (1.4%) or 10PT (<1%) regulations. By contrast, bulls with palmicorn antlers were at low risk (5.4%) to the S/F regulation, but were at high risk to the TP (19.0%) and 10PT (17.1%) regulations. The S/F regulation focused harvest on yearlings, potentially exposing 46% of yearlings to harvest. The TP and 10PT regulations targeted prime and senior bulls, potentially exposing 40-60% of those >4.5 years old to harvest. Maximum spread and shaft circumferences of antlers were significantly smaller for yearlings at risk to the S/F regulation than for their same aged counterparts not at risk. Distance between the innermost points on the brow palm was significantly larger for yearlings at risk to the S/F regulation than for yearlings not at risk. Maximum spread, shaft circumference, palm height, and width were all significantly greater for bulls at risk to the TP and 10PT regulations than for those not at risk. Distance between the innermost points on the brow palms was significantly smaller for bulls at risk to TP and 10PT regulations than for those not at risk. These findings suggest that yearling bulls with smallest antlers are most at risk to harvest by the S/F regulation, whereas largest antlered bulls are most at risk to harvest by the TP and 10 PT regulations. The consequences of this directed selection of bull moose by antler-based hunting regulations on the ...